Edukasi Koreksi Postur Terhadap Anak SMP Nurul Ilmi Kota Jambi - Hasmar, Wanti; Junaidi, Adi Saputra; Warahmah, Mawadah (Prosiding Seminar Kesehatan Nasional, 2023)
The sitting posture of the skeletal muscles (musculoskeletal) and spine, especially at the waist, must be supported by the back of a chair to avoid pain and fatigue. Based on the data collected, it was found that (80%) junior high school students who had less knowledge and had sufficient knowledge 3 (15%). After conducting counseling in an effort to correct posture, there was an increase in the knowledge of junior high school students with a percentage of 5% increasing to 90%. The aim of this counseling to the community is to increase the knowledge of junior high school students about posture correction. The implementation of counseling activities was carried out using the lecture and demonstration method with a total of 20 participants. The material presented about posture correction includes understanding, how to correct posture and the impact of wrong posture. Counseling also held discussions between the presenters and participants to share experiences related to the theme of the posture correction event. To find out the participants' understanding of the material presented, an evaluation was held by asking a number of questions. The results of this activity show an increase in junior high school students' knowledge about posture correction.Â